DESIGN AND APPLICATION OF MINI LANDSCAPE IN KARANGPRING VILLAGE TO SUPPORT ROSE AGROTOURISM PROGRAMME - Oria Alit Farisi; Susan Barbara Patricia SM; Distiana Wulanjari; Tri Handoyo (UPT Penerbitan Universitas Jember, 2022)
Roses can grow and develop well in Karangpring Village because of ecological conditions that are in accordance with the requirements for growing roses. In accordance with the roadmap, the service team in the third year will start developing Karangpring as a tourist village. This is in line with the village government's work plan which will build a typical tourist attraction in Karangpring Village. The roses, which are the superior products of Karangpring Village, do not yet have a special destination location to be visited. The superior product of Karangpring Village does not yet have a special destination location to be visited. The location planned by the village government as a tourist village object will be used as a rose cultivation land. The service team will design and implement a mini landscape that tourists can visit. This third year, the service team will work with Pokdarwis Paradis. People get additional knowledge and skills on how to make processed rose-based preparations.It is hoped that through the utilization of the village's potential as a tourist village, it will be able to increase the attractiveness of Karangpring Village, so as to be able to open market opportunities and improve the community's economy. Keywords: Roses, Cultivation, Landscape, Village Potential.